Real-time applications of machine learning in cyber physical systems - Easwaran, Balamurugan, 1975- (Advances in computational intelligence and robotics (ACIR) book series., 2022)
"This research book deals with real time applications of machine learning in cyber physical systems, for those who are working in the areas of machine learning approaches for CPS, the Internet of Things (IoT), and CPS and multidisciplinary applications of ML for CPS in the real world"--